A Financial Technology Implementation Strategy in Islamic Banking to Increase Public Financial Inclusion: SWOT Analysis at Bank Syariah Indonesia Branch Office Old Mountain - Anggi Kartika; Sarmiana Batubara (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
The financial system, particularly Islamic banking, has undergone significant changes as a result of advances in digital technology. Fintech, or financial technology, has emerged as a key tool to improve public access to formal financial services and support increased financial inclusion. However, fintech implementation in non-metropolitan areas of Indonesia continues to face several challenges, including inadequate digital infrastructure, low levels of technological literacy, and threats to digital security. By investigating the implementation of fintech in Islamic banking branches in Indonesia, this study contributes to the non-metropolitan area characterized by limited digital infrastructure. This study aims to analyze using SWOT analysis techniques to investigate how financial technology is used at Bank Syariah Indonesia KCP Gunungtua to improve financial inclusion in the community. This study combines field research methodology with descriptive qualitative methods. Five informants—Branch Operations and Service Managers, Operations Staff, Account Officers, Tellers, and Customer Service—at Bank Syariah Indonesia KCP Gunungtua were interviewed to collect research data. Using a SWOT matrix, internal and external elements were identified as part of the data analysis process. The research results show that fintech implementation has strengths in terms of ease of transaction access, service efficiency, and increased financial service reach. The main weak nesses are limited internet network s, suboptimal technological infrastructure, and low digital literacy among the public. Opportunities for fintech implementation are evident in the benefits of the Islamic banking system and the increasing public demand for digital financial services. Meanwhile, threats include the risk of cybercrime, competition between digital financial institutions, and the gap in the public's technological capabilities. Recommended strategies include strengthening digital security, increasing fintech literacy, expanding service networks through digital agents, and developing technological infrastructure in underserved areas.